Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bowed Stators on a Transonic Fan With Distorted Inlet

Abstract: The adverse impacts of inlet distortion on fan/compressor have been recognized as an important problem for several decades, and it is still a topic of considerable interest. Many research works indicate that it is possible to improve the performance and stability of a fan in clean and distorted inlet flow by using bowed stator blades. But, how bowed stator influences the flow field and what kind of bow patterns and angles can improve fan performance better are still not clearly studied. Therefore, a 3D analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Yasuo Takahashi et al [11] showed that the bowedstacking blade could weaken the vortex existing near part of the blade suction surface by lowering the blade loading in the endwall region. Peng Sun et al [12] reported that bowed stators could improve the fan performance significantly when inlet is distorted especially at design point. Comparison of rotor designs was made by John D. Denton [1], which analyzed the aerodynamic effects of lean and sweep on transonic fan performance.…”
Section: Introductionmentioning
confidence: 99%
“…Yasuo Takahashi et al [11] showed that the bowedstacking blade could weaken the vortex existing near part of the blade suction surface by lowering the blade loading in the endwall region. Peng Sun et al [12] reported that bowed stators could improve the fan performance significantly when inlet is distorted especially at design point. Comparison of rotor designs was made by John D. Denton [1], which analyzed the aerodynamic effects of lean and sweep on transonic fan performance.…”
Section: Introductionmentioning
confidence: 99%